2022
DOI: 10.1080/09585192.2022.2086438
|View full text |Cite
|
Sign up to set email alerts
|

Civilian volunteers in United Nations hot spots: what makes them intend to apply for yet another mission?

Abstract: This study focused on United Nations (UN) civilian volunteers serving in "hot spots", and tested a model to predict their intentions to apply for a new UN assignment. These individuals have characteristics of both assigned expatriates and self-initiated expatriates. In-Role Behaviours (IRB) and Organizational Citizenship Behaviours towards the Local Population (OCB-Locals) were related to sense of personal accomplishment, that in turn was related to intentions to apply for another UN assignment. Sense of perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…It is thus important to understand the dynamics that could influence the way how employees interpret and react to employer rewards in a hyper-inflationary context. Given that rewards have been accepted in literature as the primary source of employee morale (Bozionelos et al, 2022, , Chênevert, Hill & Kilroy, 2022, we are of the view that their relevance can be tested to check their effect in an inflationary context.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus important to understand the dynamics that could influence the way how employees interpret and react to employer rewards in a hyper-inflationary context. Given that rewards have been accepted in literature as the primary source of employee morale (Bozionelos et al, 2022, , Chênevert, Hill & Kilroy, 2022, we are of the view that their relevance can be tested to check their effect in an inflationary context.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Rewards have a pivotal role in inspiring workspace morale at the workplace. In fact rewards influence employee choices for preferring one employer over another (Bozionelos, Mukhuty, Kostopoulos, Bozionelos & Blenkinsopp, 2022;McWha-Hermann, Jandric, Cook-Lundgren, Carr, 2022). Truong and Barraket (2018) observed that employee morale is difficult to sustain.…”
Section: Introductionmentioning
confidence: 99%
“…Civil servants are also a group with a high commitment to the public interest [ 33 ]. High commitment and altruism motivate civil servants to tend to perform more altruistic behaviors [ 34 ]. Therefore, Civil servants are a crucial group potentially highly likely to effectively implement bystander CPR.…”
Section: Introductionmentioning
confidence: 99%